Communication Gaps Between Providers and Caregivers of Patients in a Pediatric Emergency Department. (July 2022) - Dorsey, Bridget F.; Kamimura, Akiko; Cook, Lawrence J.; Kadish, Howard A.; Cook, Heather K.; Kang, Ashley; Nguyen, Jacqueline B.T.; Holsti, Maija
Communication gaps between the healthcare team and caregivers of pediatric patients can result in negative consequences. This study aims to identify specific words and phrases used in a pediatric emergency department (ED) that are unclear or confusing to caregivers. Research assistants at the Primary Children's Hospital recorded caregivers' responses to the question, " What words or phrases have been used during this visit that are unclear or don't make sense to you?" Across all steps in the care process, 62 of 220 participants (28.2%) reported unclear words and phrases used by the healthcare team. Responses recorded after the discharge step had the highest proportion of communication problems, followed by the initial evaluation and then the update step ( χ 2 [2, N  = 220] = 6.30, P  = .043). Themes among responses included ED logistics, signs/symptoms, the diagnostic process, treatment/procedures, general confusion, and language barriers. These results provide feedback to pediatric emergency medicine providers about potential communication gaps and point to a need for further efforts to train providers in the practice of high-quality communication.